말기 신부전증 환자에서 부하 심근 SPECT 의 임상적 의의 - 김희진; Hee Jin Kim; 이태원; Tae Won Lee; 김덕윤; Deog Yoon Kim; 강흥선; Heung Sun Kang; 홍성표; Seong Pyo Hong; 임천규; Chun Cyoo Lim; et al. (The Korean journal of medicine, 1999)
Background : Coronary artery disease(CAD) is a leading cause of death in patients with end-stage renal disease(ESRD). Current data concerning the role of dipyridamole SPECT myocardial imaging for the diagnosis of CAD in patients with ESRD vary according to authors. This study was performed to evaluate the usefulness of dipyridamole SPECT myocardial imaging and coronary angiography in diagnosing the CAD in patients with ESRD. Methods : Sixty-three patients with ESRD underwent dipyridamole SPECT myocardial imaging and sixteen with positive myocardial imaging had selective coronary angiography. Controls were 73 patients with normal renal function who had dipyridamole SPECT myocardial imaging and coronary angiography because of chest pain or discomfort. The perfusion defect in myocardial images were defined as reversible or irreversible. Significant coronary artery disease was defined as one or more vessel disease with at least 50% stenosis on coronary angiography. The correlation between regional imaging defects and coronary stenoses in the corresponding vascular distribution was determined by the rule of a Van Train. Results : Forty-nine of the patients had abnormal myocardial images (16 reversible, 6reversible + irreversible, 27 irreversible defects). Twenty six patients had a left anterior descending artery(LAD) defect, 13 a left circumflex artery(LCX) defect, 26 a right coronary artery(RCA) defect. There were no differences in age, sex, type and duration of dialysis, and associated atherogenic risk factors between patients with positive and negative myocardial imaging except for the durations of diabetes. Ten of the 16 patients, and thirty-nine of the 45 controls with positive myocardial imaging had a 50% or greater stenosis of one or more coronary arteries in coronary angiography. Therefore, the predictive value of positive SPECT in patients with ESRD was 63%, and that of controls was 87%. Of the 10 patients with stenotic lesions, 6 had double-, 3 single-, and 1 triple-vessel disease. Altogether, 7 diseased LCX , 6 RCA, and 5 LAD were found. In contrast, Of the 39 controls with angiographically significant stenotic lesions, 24 had single-, 9 double-, and 6 triple -vessel disease. Altogether, 27 diseased LAD, 17 LCX, and 16 RCA were found. There were no differences in age, sex, type and duration of dialysis, ST-T waves change, duration of ESRD, associated atherogenic risk factors, LV mass index and LVH between the patients with and without CAD except for the history of smoking. Three of 6 patients with false positive results of myocardial images had inferior perfusion defect and were on peritoneal dialysis. The pressure effects of peritoneal fluids on inferior perfusion defect were proven by a significant change of disappearance of inferior perfusion defect in myocardial images after complete drainge of the peritoneal fluids. And, the predictive value of positive SPECT differed between patients with and without false positive results of myocardial images (predictive value of positive SPECT 63% and 77%, respectively). Conclusion : Dipyridamole SPECT myocardial imaging appears to be an useful method for detection and exclusion of CAD in patients with ESRD and interpretation of dipyridamole SPECT myocardial imaging with inferior perfusion defect in patients with continuous ambulatory peritoneal dialysis needs more caution.(Korean J Med 57:1037-1047, 1999)